Análisis De La Influencia Del Control Interno En Los Emprendimientos Del Barrio San Jose Sur De Bogotá. (2022)
In some or most ventures are carried out by people who have the basic knowledge about the process of the good or service they want to provide, however, they lack understanding regarding the operation and optimal control of their business idea; because your initial motivation lies in the needs and experiences you have had throughout your life; from here, the entrepreneur generates certain empirical knowledge that could cause failure on some occasions.